Correction to: Circular RNA profiling and its potential for esophageal squamous cell cancer diagnosis and prognosis - Liyuan Fan; Qiang Cao; Jia Liu; Junpeng Zhang; Baosheng Li (Molecular Cancer, 2020)
An amendment to this paper has been published and can be accessed via the original article.